Poly[diaqua(μ(4)-carboxylatomethylphosphonato)(μ(4)-carboxymethylphosphonato)pentadecamethylpentatin(IV)] - Boye, Mouhamadou Sembene (International Union of Crystallography, 2013)
The central Sn(IV) atom of the pentanuclear title complex, {[Sn(CH(3))(3)](3)O(2)C(CH(2))PO(3)[Sn(CH(3))(3)(H(2)O)](2)HO(2)C(CH(2))PO(3)}, is located on a twofold rotation axis; due to symmetry, the H atom of the carboxyl group of the anion is disordered with a site occupancy of 0.5. The central Sn(IV) atom is bonded to three methyl groups (one of which is disordered about the twofold rotation axis) and is symmetrically trans coordinated by two phosphonate groups with Sn—O = 2.2665 (12) Å while the other SnMe(3) residues are asymmetrically trans coordinated with Sn—O = 2.1587 (12) and 2.3756 (13) Å for one residue and Sn—O = 2.1522 (12) and 2.4335 (12) Å for the other; the Sn–O distances involving two O atoms trans to carboxylate are longer than those trans to phosphonate groups. The Sn—C distances lie in a very narrow range [2.112 (2)–2.133 (3) Å]. The oxyanion behaves as a tetra-coordinating ligand. The bridging mode of the latter leads to the formation of layers parallel to (001) that are interconnected by O—H⋯O and C—H⋯O hydrogen bonds.